Factors Affecting the Quality of Financial Statements: Information Technology, Competence of Human Resources and Internal Control Systems - Elgy Andrian; Cris Kuntadi (Dinasti International Journal of Education Management And Social Science, 2023)
Previous or relevant research is fundamental in a research or scientific article. That research strengthens the theory and phenomenon of relationships or influences between variables. This article reviews the factors that affect the quality of financial statements, namely: Information Technology, Human Resources Competence, and Internal Control Systems, in a literature study of State Financial Management. This article aims to build a hypothesis of the influence between variables to be used in future research. The results of this literature review article are 1) Information Technology affects the quality of financial statements, 2) Human Resource Competence affects the quality of financial statements, and 3) The Internal Control System affects the quality of financial statements.